Red Jenkinson: Tracing Indigenous Influences on Canadian Archival Theory - Frogner, Raymond (Archivaria)

(untitled) (Association of Canadian Archivists, 2025)
This article considers an Indigenous imaginative thread in the dominant European intellectual history of colonization in Canada. Until recently, historiography of the colonial encounter commonly assumed the dominance of imperial imagination was an unchallenged cognitive event. European intellectual histories have proven reluctant to recognize the sustained independence and holistic self-reliance of Indigenous knowledge models or the Indigenous influences on European thought. However, European juridical knowledge paradigms have never eliminated those collective cognitive social principles that supported Indigenous societies for generations before first contact. This Indigenous epistemological influence can be found in our institutions of governance; in our mechanisms of social representation; and in our public spaces of culture, heritage, and social memory.This article first considers how Indigenous spiritual epistemologies, social protocols, and knowledge methods were delegitimized and marginalized by Enlightenment thinkers. Next, it looks at the Kwakwaka’wakw encounter, when George Hunt and Franz Boas recorded resistant and independent Indigenous cosmologies in late-19th-century West Coast Indigenous communities. Through ceremony, Indigenous authorities demonstrated core values of Indigenous cosmologies: the potential of diversity over the threat of difference; the dynamism of culture; and the holistic vision of totemic, collective relationships between humanity and nature. From here, the article examines how mid- century critical theory carved out a theoretical space for these Indigenous values for humanity. Finally, it looks at how Indigenous cosmologies have begun to break through constraining modernist traditions of archival remembrance. The article closes with the notion of the decolonizing of archives and the digital potential for new, post-colonial archival paradigms that recognize revitalized Indigenous epistemologies.